Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Rumah KPR Bersubsidi Pada PT. Dyas Property Di Kota Mataram - Sudirman, Sudirman; Budiarti, Ni Luh Rina; Mardiah, Ananda; Furkan, Lalu M.; Sjah, Taslim (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
This study aims to analyze the marketing strategy used by PT Dyas Property in promoting the subsidized mortgage housing product “Pesona Bukit Haniffa” to maximize profits. A qualitative descriptive method was employed using primary and secondary data sources. The variables analyzed include place, price, product, and promotion, along with segmentation, targeting, and positioning (STP) strategies. Results show that PT Dyas Property effectively applied the 4P marketing mix and STP strategies. The houses are built with quality materials, offered at affordable prices and down payments, located strategically in Praya District near RSUD Praya, and promoted through social media and experiential marketing. The chosen market segment focuses on RSUD Praya employees who do not yet own a home, positioning the product under the subsidized mortgage brand "Pesona Bukit Haniffa" with the tagline "a comfortable and beautiful home." It is recommended that the company initiate earlier promotions or offer early bird programs before construction is completed.